2021
DOI: 10.3390/wevj12030106
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Humidity Dynamics for Open-Cathode Proton Exchange Membrane Fuel Cell

Abstract: The durability and output performance of a fuel cell is highly influenced by the internal humidity, while in most developed models of open-cathode proton exchange membrane fuel cells (OC-PEMFC) the internal water content is viewed as a fixed value. Based on mass and energy conservation law, mass transport theory and electrochemistry principles, the model of humidity dynamics for OC-PEMFC is established in Simulink® environment, including the electrochemical model, mass flow model and thermal model. In the mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…As can be observed, an increase in current input leads to a decrease in the membrane water content. In their work regarding modeling humidity dynamics of an opencathode PEM fuel cell, Chen et al [16] observed similar dynamics of membrane water content in response to an increase in current. Karthik and Vijayachitra [26] and Chen et al After validating the thermal and voltage predictions of GT-Suite, its membrane water content was used to validate the physics-based water management model.…”
Section: Lumped Model Validationmentioning
confidence: 86%
See 1 more Smart Citation
“…As can be observed, an increase in current input leads to a decrease in the membrane water content. In their work regarding modeling humidity dynamics of an opencathode PEM fuel cell, Chen et al [16] observed similar dynamics of membrane water content in response to an increase in current. Karthik and Vijayachitra [26] and Chen et al After validating the thermal and voltage predictions of GT-Suite, its membrane water content was used to validate the physics-based water management model.…”
Section: Lumped Model Validationmentioning
confidence: 86%
“…To study and control the cathode humidity of a PEM fuel cell, Chen et al [15] developed a dynamic water management model and applied an active disturbance control strategy. Chen et al [16] developed a lumped parameter control-oriented model for predicting humidity dynamics for an opencathode PEM fuel cell. Based on their model, the output performance of an open-cathode PEM fuel cell, taking into account the internal humidity state of the stack, is predicted.…”
Section: Introductionmentioning
confidence: 99%
“…In the context where 𝑉 𝐹𝐶 denotes the output voltage of the fuel cell, 𝐸 𝑁𝑒𝑟𝑛𝑠𝑡 is the symbol employed to depict the thermodynamic potential and reversible voltage of the fuel cell [22], which equivalently represents its output voltage. Nevertheless, the actual output voltage is diminished owing to diverse voltage losses.…”
Section: Simulation Model Of Oc-pem Fuel Cellmentioning
confidence: 99%
“…Furthermore, membrane drying will also lead to localized hot spots [8], which causes damage to the PEM such as perforation or delamination. In the contrary, too high water content will leave the membrane in a "flooding" state, which will block porous channels and reduce the rate of reactant transport [9][10][11]. It has been shown that improper humidity of the PEM not only degrades the performance of the fuel cell and reduces the power generation efficiency but also leads to irreversible degradation of its internal components (e.g., the catalyst and membrane).…”
Section: Introductionmentioning
confidence: 99%